Attitudes Toward Delegation to Presidential Commissions. Issue 3 (4th July 2017) - Miller, David R.; Reeves, Andrew
Abstract : We examine attitudes of the pubic toward delegation to presidential commissions. In four survey experiments across a range of contexts, we compare the public response to the creation of a commission to that of a direct presidential action. We find that there is no significant difference in the approval garnered for taking action alone or delegating the decision to a presidential commission. This is true whether this is at the policy formulation stage or implementation stage. Additionally, we do not find that policies formed by commissions are seen as any more effective than those policies formed by the president alone.